ECOTOXICITY STUDIES OF PYRIDINIUM BASED IONIC LIQUIDS - MOHAMED HAFEZ, NEHAL FAROUK (2016)
Ionic liquids (ILs) are an interesting group of compounds that possess special properties making them a potential replacement for hazardous organic solvents in industry. Notably, the usage of pyridiniurn ILs has been reported widely for different chemical and biological applications. However, the aquatic toxicity data of these compounds are not available. An adequate process design using this group of chemicals requires the assessment of the ecotoxicological risks of these chemicals. The aim is to assess the aquatic toxicity of pyridiniurn ILs using the acute toxicity test towards vital environmental elements such fish and bacteria. In this study, 22 pyridiniurn ILs with various alkyl chain lengths were synthesized using conventional and microwave-assisted techniques. Characterization data was obtained using 'H NMR and l3C NMR. The toxicity evaluation was performed based on Organisation for Economic Cooperation and Development (OECD) Guidelines towards guppy fish.